OPTIMALISASI PEMILIHAN TOPIK PENELITIAN ILMIAH YANG EFEKTIF UNTUK PENELITI DI SAINS ORGANISASI - Abdillah, Muhammad Rasyid; Anita, Rizqa (Komunitas Manajemen Kompetitif, 2024)
Selecting research topics is a crucial step in scientific inquiry, especially for producing impactful studies. This community service program aimed to enhance researchers' understanding of five key criteria: relevance to grand challenges, contributions to academic discussions, engagement with the scientific community, broad scope, and practical value. Conducted at a state university (ABC University [anonymous]) in the Riau Islands, the workshop involved 11 priority researchers. Pretest and posttest evaluations showed significant improvement in participants’ understanding. This program highlights the importance of targeted training in helping researchers address editorial challenges and achieve higher acceptance rates in reputable journals.